MAGNETOSTRATIGRAPHY OF THE HOMO-BEARING PLEISTOCENE DANDIERO BASIN (DANAKIL DEPRESSION, ERITREA) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
Four magnetozones have been found in the 530 m thick profile of the Dandiero Group. The lower unit, the Bukra Sand and Gravel, extends in the R1 reversed magnetozone from 150 m below the tephra level which was used as the reference marker between the sampled sections. The normal magnetozone N1 is almost completely covered by the lacustrine and deltaic sediments of the Alat Formation, while the following reversed magnetozone contains both the Wara Sand and Gravel and the lacustrine Goreya Fm. The N2 polarity zone is completely occupied by the Aro Sand. This polarity sequence has been calibrated to the geomagnetic time scale using the Early to Middle Pleistocene age of the associated vertebrate fauna and fission-track dating. The four magnetozones were thus regarded as representing the chrons by which the Pleistocene is correlated with magnetochronology. Their three reversal boundaries provided the dates of 1.07, 0.99 and 0.78 Ma, allowing to determine average sedimentation rates close to 1 m/ky. Cyclostratigraphy of the magnetic signal, analysed by the spectral analysis of the time series across the Jaramillo and late Matuyama chrons, confirmed that value. The evidenced cyclicities were directly related to the alternating lithofacies, and both to the astronomical parameters driving the climate changes during the deposition of the Dandiero group (some five hundred thousand years). The section with the Homo site covers the Jaramillo/Matuyama boundary, and the Homo bed located 2 m below this limit is dated 0.992 Ma.